(S)-5-Hexyl-1-[(S)-2-hydroxy-1-phenylethyl]-4-methoxy-1H-pyrrol-2(5H)-one - Zheng, Jian-Feng (International Union of Crystallography, 2009)
The title compound, C(19)H(27)NO(3), was obtained by the reaction of (3S,7aR)-7a-hexyl-7-methoxy-3-phenyl-2,3-dihydropyrrolo[2,1-b]oxazol-5(7aH)-one and triethylsilane using titanium(IV) chloride as catalyst. In the molecule, the phenyl and dihydropyrrolone rings form a dihedral angle of 83.8 (1)°. O—H⋯O hydrogen-bonding interactions lead to the formation of a chain parallel to the a axis.